Real-world outcomes from a series of patients with late onset Pompe disease who switched from alglucosidase alfa to avalglucosidase alfa - Carter, Chris; Boggs, Tracy; Case, Laura E.; Kishnani, Priya (Frontiers in Genetics, 2024)
Pompe disease is an inherited, progressive neuromuscular disorder caused by deficiency of lysosomal acid ɑ-glucosidase and accumulation of glycogen in tissues, resulting in cellular dysfunction, muscle damage, and functional disabilities. Enzyme replacement therapy with alglucosidase alfa (Myozyme/Lumizyme) has led to better outcomes, but many patients have plateaued or declined despite treatment. The second-generation ERT avalglucosidase alfa (Nexviazyme) was designed to have enhanced cellular uptake via the conjugation of additional bis-mannose-6-phosphate residues. There have been trials comparing the efficacy of alglucosidase and avalglucosidase, but there remains a need for more real-world data on patients who switched from alglucosidase to avalglucosidase. A chart review was conducted on n=15 patients with late-onset Pompe disease followed at a single center who switched from alglucosidase to avalglucosidase and continued for at least 6 months. A total of n=8/15 patients received alglucosidase for more than three years prior to switching, and n=7/15 received it for more than five years prior to switching. There were statistically significant improvements in CK, Hex4, and AST with mean differences of -104.8 U/L, -3.0 mmol/molCr, and -14.7 U/L, respectively, post-switch. 6-Minute Walk Test; comfortable gait speed; Gait, Stairs, Gower, Chair; and Quick Motor Function Test scores improved or stabilized in most patients post-switch (n=8/12, n=11/12, n=9/12, n=7/11, respectively). Of n=7 patients with pulmonary function testing, n=4/7 had improved upright FVC. Patient-reported outcomes revealed improvements in dyspnea (n=4/4), physical function (n=3/4), fatigue (n=2/3), and lower back pain (n=3/3). Avalglucosidase was well tolerated without infusion-associated reactions, and all n=7 patients on home infusions continued receiving ERT at home. Anti-drug antibodies were seen in n=9/10 of patients on alglucosidase and n=8/13 of those on avalglucosidase, with titers below 12,800 in a majority of patients. We also present the first outcome data for a patient with LOPD who is non-ambulatory and a full-time wheelchair user; she demonstrated meaningful improvements in quality of life and motor function with the switch. In summary, improved outcomes were seen in most patients, with a subset whose decline persisted. This study presents evidence that switching from alglucosidase to avalglucosidase may be associated with improved outcomes in certain patients with LOPD.